Analisis Kesuksesan Inkubator dan Akselerator Bisnis Dalam Membangun Startup - Yunika, Karina; Dewanti, Ida Susi; Indarwanta, Didik (Jurnal Paradigma, 2024)
This study aims to determine the success of incubators and accelerators in building startups. This type of research is descriptive research with a qualitative approach. Data obtained through observation and in-depth interviews. The research data analysis technique was carried out using the Miles and Huberman model which consisted of three stages, namely; data reduction, data display, and conclusion/verification. Analysis activities are carried out from data collection to drawing conclusions. The results showed that PT Gama Inovasi Berdikari's assessment met the characteristics of the accelerator program including: Program Structure, Operational Features, Financial Capital & IP Rights, Social Capital & Networking. Next is the impact received by the assisted startups after participating in the accelerator program, namely: increasing education related to startups, having a forum or place for innovation related to startups, startups participating in the accelerator and incubator programs at PT Gama Inovasi Berdikari get quite a positive impact, get directions to run the company, looking for investors, from a legal perspective, providing support, managing investments, and maintaining valuations. Based on the results of the research, it can be concluded that PT GIB has succeeded in providing the program as desired by startups with programs that have been designed by PT GIB through the selection process, support services, and network owned by PT GIB